2012
DOI: 10.1111/odi.12018
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in the oral cavity of healthy Chinese Han children

Abstract: Although there was interindividual variation in the oral microflora, some bacterial genera were conserved among individuals, supporting the existence of a core microbiome in the oral cavity of healthy Chinese Han children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
0
23
1
Order By: Relevance
“…Crielaard et al (2011) studied the saliva microbiomes of 3-18-year-old children, revealing that maturation of the microbiome is driven by biological changes with age. Xin et al (2013) reported the dental plaque diversity of healthy Chinese Han children aged 6-8 and supported the existence of a "core microbiome". Xu et al (2015) explored the significantly different microbial communities of different niches, and the results were consistent with the results of the HMP (Human Microbiome Project, 2012b).…”
Section: Introductionmentioning
confidence: 95%
“…Crielaard et al (2011) studied the saliva microbiomes of 3-18-year-old children, revealing that maturation of the microbiome is driven by biological changes with age. Xin et al (2013) reported the dental plaque diversity of healthy Chinese Han children aged 6-8 and supported the existence of a "core microbiome". Xu et al (2015) explored the significantly different microbial communities of different niches, and the results were consistent with the results of the HMP (Human Microbiome Project, 2012b).…”
Section: Introductionmentioning
confidence: 95%
“…Based upon the existing literature that supports that young individuals and adolescents harbor many of the oral microorganisms considered to contribute to periodontitis in adults (12, 19, 20), and generally demonstrate a high prevalence of gingivitis, it is very infrequent that they develop destructive periodontitis (20). This report posits that the lack of progression of chronic inflammation in young individuals to a tissue destructive process that is the hallmark of periodontitis, will be reflected by differential expression of genes in response to the bacterial biofilm challenge that are more tissue protective and help maintain the integrity of the tissues even in the presence of persistent inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the oral microbiome is acquired early in life and varies among individuals, including in the types of commensal bacteria that are present, as well as in the quality and quantity of proposed opportunistic pathogens that trigger periodontitis later in life (10)(11)(12)(13). There is minimal evidence that these pathogens are acquired exogenously in adults who develop periodontitis; accordingly, research has attempted to focus identification of risk by examining local inciting or environmental factors that would help to trigger the changes in prevalence and composition of bacteria responsible for periodontal disease and identifying genetic polymorphisms that could contribute to dysfunctional responses in the periodontium to the microbial challenge.…”
mentioning
confidence: 99%
“…However, very few oral microbiome studies in healthy children have been performed so far (Papaioannou et al, 2009; Xin et al, 2013), some including pyrosequencing (Crielaard et al, 2011; Stahringer et al, 2012; Ling et al, 2013; Lif Holgerson et al, 2015). The study design of Crielaard et al differs from ours in that they investigated microbial profiles of saliva collected from caries-diseased Dutch children aged 3–18 years.…”
Section: Discussionmentioning
confidence: 99%
“…This can be illustrated by the example of just 10 published manuscripts dealing with the collection of samples from an intact oral cavity. They report using saline oral wash rinse (Ahn et al, 2011) or unstimulated whole saliva (Xin et al, 2013) for fluid collection; dental explorers (Xin et al, 2013), metal loops (Ling et al, 2010), metal curettes (Papaioannou et al, 2009) and wooden tooth picks (Keijser et al, 2008) for supragingival sampling; or wet and dry swabs and brushes (Aas et al, 2005; Papaioannou et al, 2009; Cortelli et al, 2012) and spatulas (Gohler et al, 2014) for mucosal sampling. Finally, subgingival sampling is currently being performed using either metal curettes (Papaioannou et al, 2009; Abusleme et al, 2013) or paper points (Cortelli et al, 2012; Griffen et al, 2012; Jünemann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%